(−)Epigallocatechin-3-gallate decreases the stress-induced impairment of learning and memory in rats. (18th August 2015) - Soung, Hung-Sheng; Wang, Mao-Hsien; Tseng, Hsiang-Chien; Fang, Hsu-Wei; Chang, Kuo-Chi
Highlights: Stress decreased the locomotor activity and impaired the spatial memory in rats. EGCG enhanced the locomotor activity in stressed rats. EGCG improved the learning and memory of stressed rats. EGCG reduced the hippocampal oxidation state in stressed rats. The results suggest that EGCG has a therapeutic effect on stress-induced impairment. Abstract: Stress induces reactive oxygen species (ROS) and causes alterations in brain cytoarchitecture and cognition. Green tea has potent antioxidative properties especially the tea catechin (-) epigallocatechin-3-gallate (EGCG). These powerful antioxidative properties are able to protect against various oxidative damages. In this study we investigated the impact of stress on rats' locomotor activity, learning and memory. Many tea catechins, including EGCG, were examined for their possible therapeutic effects in treating stress-induced impairment. Our results indicated that locomotor activity was decreased, and the learning and memory were impaired in stressed rats (SRs). EGCG treatment was able to prevent the decreased locomotor activity as well as improve the learning and memory in SRs. EGCG treatment was also able to reduce the increased oxidative status in SRs' hippocampi. The above results suggest a therapeutic effect of EGCG in treating stress-induced impairment of learning and memory, most likely by means of its powerful antioxidative properties.